Effect of coating on permeability and selectivity of polysulfone membrane for CO2/CH4 separation - Nurul Basyirah, Samat (2010)
Polysulfone membrane is one of the potential candidates to be used as membranes for gas separation. Asymmetric ysulfone (PSU) membranes were fabricated through a simple dry/wet phase inversion process. Casting solution developed in this study consisted of polysulfone, N-N imethylacetamide (DMAc) and ethanol. The dope solution was divided into three polymer composition which is 20 wt%, 25 wt% and 30 wt%. The dope solution was cast using manual casting knife at room temperature. Three membrane samples was produced with different polymer composition; uncoated membrane (A), membrane coated with bromine and treated with methanol (B) and membrane coated with bromine without methanol treatment (C). Permeability of the membrane was examined by using gas permeation test with pure CO 2 and C14 4 as tested gas. The results showed that the selectivity of the PSU membrane increased respectively with the decreasing of polymer concentration and coating treatment have a significant effect on membrane performance. The best membrane selected is membrane B which is polysulfone membrane with 20 wt% polymer composition treated with methanol and coated with .bromine. From the data and supported theories by various authors, it can be conclude that coating treatment have a significant effect on membrane performance.